Overexpression of a SBP-Box Gene (VpSBP16) from Chinese Wild Vitis Species in Arabidopsis Improves Salinity and Drought Stress Tolerance - Hou, Hongmin (Int J Mol Sci, 2018)
Salinity and drought are two major abiotic stresses that limit grape productivity. Responses to stress in grape are known to be regulated by several families of transcription factors. However, little is known about the role of grape Squamosa promoter binding protein (SBP)-box transcription factor genes in response to abiotic stress. To better understand the functions of the grape SBP-box genes in abiotic stress tolerance, a full-length complementary DNA (cDNA) sequence of the putative SBP-box transcription factor gene, VpSBP16 was amplified from Chinese wild grapevine Vitis pseudoreticulata clone “Baihe-35-1”. We observed that the VpSBP16 protein fused to the green fluorescent protein (GFP) reporter accumulated in the nucleus when transiently expressed in onion epidermal cells. Moreover, VpSBP16 was shown to have transcriptional activation activity using a yeast trans-activation assay. We performed a VpSBP16 functional analysis through the characterization of transgenic Arabidopsis thaliana plants constitutively over-expressing VpSBP16. The transgenic lines had longer roots and the seeds had a higher germination rate than the wild type (WT) under osmotic stress. In addition, the accumulation of reactive oxygen species (ROS) of transgenic seedlings was significantly lower than WT in the transgenic lines, as was electrolyte leakage. VpSBP16 overexpression also elevated expression levels of stress-response genes involved in the salt overly sensitive (SOS) pathway. These results indicate that overexpression VpSBP16 in A. thaliana enhances tolerance of salt and drought stress during seed germination, as well in seedlings and mature plants, by regulating SOS and ROS signaling cascades.